Conservation and repair of a historical masonry ruin belonging to the Middle Byzantine Era: The case of ruined cistern unearthed in the Çobankale archeological site (Yalova, Turkey). (July 2022) - Seçkin, Selçuk; Sayin, Baris
Abstract: The current study presents a four-step methodological approach for the conservation and repair of a Middle Byzantine Era cistern. In the first stage of the study, the samples gathered from different parts of the ruin were subjected to physical and chemical analyzes. In the second stage, the material compositions were determined by evaluating the data obtained by the analyses. Then, the seismic performance level of the cistern was determined through linear, pushover, and kinematic limit analyses. With these analyses, story displacements, shear forces, and story drifts were determined and compared with the values set forth in the seismic code. In the last step, conservation and repair practices were performed considering the data obtained in the previous stages. Accordingly, a cultural asset belonging to the Middle Byzantine era was consolidated and repaired that would contribute to cultural tourism in the region. The current study is believed to make a valuable contribution to the literature and guide academics and designers since it presents all critical stages of a conservation and repair process for a buried ruined structure.